Enhanced Cellular Uptake and Transport of Bovine Lactoferrin Using Pectin- and Chitosan-Modified Solid Lipid Nanoparticles - Xudong Yao; Craig Bunt; Mengyang Liu; Siew-Young Quek; John Shaw; Jillian Cornish; Jingyuan Wen (MDPI AG, 2023)
Aim: The aim of this project is to use pectin- and chitosan-modified solid lipid nanoparticles for bovine lactoferrin to enhance its cellular uptake and transport. Methods: Solid lipid particles containing bovine lactoferrin (bLf) were formulated through the solvent evaporation technique, incorporating stearic acid along with either chitosan or pectin modification. bLf cellular uptake and transport were evaluated in vitro using the human adenocarcinoma cell line Caco-2 cell model. Results and Discussion: The bLf-loaded SLPs showed no significant effect on cytotoxicity and did not induce apoptosis within the eight-hour investigation. The use of confocal laser scanning microscopy confirmed that bLf follows the receptor-mediated endocytosis, whereas the primary mechanism for the cellular uptake of SLPs was endocytosis. The bLf-loaded SLPs had significantly more cellular uptake compared to bLf alone, and it was observed that this impact varied based on the time, temperature, and concentration. Verapamil and EDTA were determined to raise the apparent permeability coefficients (App) of bLf and bLf-loaded SLPs. Conclusion: This occurred because they hindered efflux by interacting with P-glycoproteins and had a penetration-enhancing influence. These findings propose the possibility of an additional absorption mechanism for SLPs, potentially involving active transportation facilitated by the P-glycoprotein transporter in Caco-2 cells. These results suggest that SLPs have the potential to be applied as effective carriers to improve the oral bioavailability of proteins and peptides.